Synergistic Integration of Liner Shipping and Economic Development - Edvard Roškar; Jelenko Švetak (Promet (Zagreb), 2008)
Liner shipping with all its specific features plays an importantrole in the economic development of a country whose portsare involved. In the strategic goals of maritime policy for the period2005-2009 the European Commission stresses the needfor a sustainable environmental development and economicgrowth. Besides, it points out the necessity for the fulfilment ofall maritime potentials. Yet, individual EU member states frequentlycreate the environment, which discourages the developmentof their own national maritime economy. Unfortunately,this applies also to the Republic of Slovenia. The current paperoffers a detailed analysis of the weaknesses and benefits of theclassical liner shipping in present day.